Pengaruh Latar sosial Terhadap Kondisi Psikologis Tokoh Meg Murry dalam Novel A Wriinke In Time - Putri Libria (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2023)
This study aims to describe character personality of main character because affected of social background in the novel A Wrinkle in Time. Both of which is main problem in the novel. The method used in this research is descriptive qualitative method, with using psychology literature approach based on Shaw and Costanzo as a main theoritical basis for this research. The data of this study were taken from A Wrinkle in Time Novel. In generally this research discusses about the main character which through a life-long process of self-seeking. Her character was changes when her dad were gone. She feels deeply insecure about her personal appearance, then people around her think she’s has bad personality and ugly. The results of this research is describe social background that affects the psychological condition of main character in the novel A Wrinkle in Time.